2011
DOI: 10.1109/tasc.2010.2090439
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Effect on the Structural and Electrical Properties of Sputtered YBCO Coated Conductors

Abstract: In this paper we studied the structural and electrical properties variations with the thickness of YBa 2 Cu 3 O 7 X (YBCO) film. In our experiments, the critical current density (Jc) has a maximum at 1.2 micron rather than monotonically decreased with increasing film thickness. The in-plane and out-plane alignments of the films, measured with X-ray Diffraction Omega-scan and Phi-scan, were poor at the beginning stage of the deposition and then became better as the film thickness increased.The surfaces of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…They associated the pinholes with stronger oriented grains along the c -axis [14]. Tao et al [15] (by sputtering method, in their Figure seven), Chen et al [16] (by advanced low-fluorine solution method, in their Figure four), and Vermeir et al [17] (by fluorine-free water-based sol–gel method, in their Figure five) also reported a similar pinhole appearance. In another series of experiments for GdBCO films deposited with different temperatures, we find that a higher temperature favors the emergence of pinholes while a lower temperature favors a flat film without pinholes.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…They associated the pinholes with stronger oriented grains along the c -axis [14]. Tao et al [15] (by sputtering method, in their Figure seven), Chen et al [16] (by advanced low-fluorine solution method, in their Figure four), and Vermeir et al [17] (by fluorine-free water-based sol–gel method, in their Figure five) also reported a similar pinhole appearance. In another series of experiments for GdBCO films deposited with different temperatures, we find that a higher temperature favors the emergence of pinholes while a lower temperature favors a flat film without pinholes.…”
Section: Resultsmentioning
confidence: 88%
“…Tao et al [15] reported the J c of YBCO film to be 1.6 × 10 6 A/cm 2 at 77 K and self-field with a thickness of 1.2 μm by sputtering method on buffered Ni-5 at.% W substrates. Tran et al [23] found that the 0.2-μm-thick GdBCO film had the highest J c of 3.8 × 10 6 A/cm 2 and the J c value decreased to 4.2 × 10 5 A/cm 2 as the film thickness increased to 0.55 μm.…”
Section: Resultsmentioning
confidence: 99%